2D Free‐Standing Nitrogen‐Doped Ni‐Ni3S2@Carbon Nanoplates Derived from Metal–Organic Frameworks for Enhanced Oxygen Evolution Reaction. Issue 18 (8th April 2019) - Lin, Yifan; Chen, Gen; Wan, Hao; Chen, Fashen; Liu, Xiaohe; Ma, Renzhi
Abstract: 2D metal–organic frameworks (2D MOFs) are promising templates for the fabrication of carbon supported 2D metal/metal sulfide nanocomposites. Herein, controllable synthesis of a newly developed 2D Ni‐based MOF nanoplates in well‐defined rectangle morphology is first realized via a pyridine‐assisted bottom‐up solvothermal treatment of NiSO4 and 4, 4′‐bipyridine. The thickness of the MOF nanoplates can be controlled to below 20 nm, while the lateral size can be tuned in a wide range with different amounts of pyridine. Subsequent pyrolysis treatment converts the MOF nanoplates into 2D free‐standing nitrogen‐doped Ni‐Ni3 S2 @carbon nanoplates. The obtained Ni‐Ni3 S2 nanoparticles encapsulated in the N‐doped carbon matrix exhibits high electrocatalytic activity in oxygen evolution reaction. A low overpotential of 284.7 mV at a current density of 10 mA cm −2 is achieved in alkaline solution, which is among the best reported performance of substrate‐free nickel sulfides based nanomaterials. Abstract : Controllable synthesis of a newly developed 2D Ni‐based metal–organic framework (MOF) nanoplates with a well‐defined rectangle morphology is first realized via a pyridine‐assisted bottom‐up solvothermal treatment of NiSO4 and 4, 4′‐bipyridine. Subsequent "self‐sulfidation" treatment converts the MOF nanoplates into 2D free‐standing nitrogen‐doped Ni‐Ni3 S2 @carbon nanoplates, which can be used as an efficient electrochemical catalyst in oxygen revolution reaction.